Renal Clearable Gold Nanoparticle-Functionalized Silk Film for in vivo Fluorescent Temperature Mapping - Hua, Wei; Mao, Yusheng; Zhang, Jinzhu; Liu, Lang; Zhang, Guolin; Yang, Shengyang; Boyer, Daniel; Zhou, Chen; Zheng, Fenfen; Sun, Shasha; Lin, Shengling (Frontiers in Chemistry, 2020)
Implantable optical sensing devices that can continuously monitor physiological temperature changes hold great potential toward applications in healthcare and medical field. Here, we present a conceptual foundation for the design of biocompatible temperature sensing device by integrating renal clearable luminescent gold nanoparticles (AuNPs) with silk film (AuNPs-SF). We found the AuNPs display strong temperature dependence in both near-IR fluorescence intensity and lifetime over a large temperature range (10-60 °C), with a fluorescence intensity sensitivity of 1.72%/°C and lifetime sensitivity of 0.09 μs/°C. When integrated the AuNPs with biocompatible silk film and implanted in the dorsal region of mice, the fluorescence imaging of the AuNPs-SF in the body shows a linear relationship between the average fluorescence intensity and temperature. More importantly, less than 3.68% ID gold are left in the body and no adverse effect is observed for 8 weeks. This AuNPs-SF can be potentially used as a flexible, biocompatible and implantable sensing device for in vivo temperature mapping.